2021
DOI: 10.1097/yco.0000000000000733
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota and microbiome in schizophrenia

Abstract: Purpose of review Accumulating evidence indicates that there are bidirectional interactions between the gut microbiota and functioning of the central nervous system. Consequently, it has been proposed that gut microbiota alterations might play an important role in the pathophysiology of schizophrenia. Therefore, in this article, we aimed to perform a narrative review of studies addressing gut microbiota alterations in patients with schizophrenia that were published in the years 2019–2020. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…For one thing, our result suggests that uncovering the variability of gut flora by sub-classifying the patients according to aggression presence or absence is warranted. For another, it also implies that correction of gut dysbiosis in aggression-affected ScZ inpatients using adjunct therapy with probiotics may achieve limited efficacy due to the variability in several bacteria besides Bifidobacterium, which is a verified speculation in some psychiatric disorders including ScZ [ 27 , 28 ]. But from another point of view, emerging evidence confirmed the pro-inflammation properties of genera Prevotella [ 29 31 ], and anti-inflammation properties of genera Bacteroides , Faecalibacterium , Blautia, Bifidobacterium and Collinsella [ 31 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…For one thing, our result suggests that uncovering the variability of gut flora by sub-classifying the patients according to aggression presence or absence is warranted. For another, it also implies that correction of gut dysbiosis in aggression-affected ScZ inpatients using adjunct therapy with probiotics may achieve limited efficacy due to the variability in several bacteria besides Bifidobacterium, which is a verified speculation in some psychiatric disorders including ScZ [ 27 , 28 ]. But from another point of view, emerging evidence confirmed the pro-inflammation properties of genera Prevotella [ 29 31 ], and anti-inflammation properties of genera Bacteroides , Faecalibacterium , Blautia, Bifidobacterium and Collinsella [ 31 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, gut microbiota may become a potential therapeutic strategy for TRS. Gut microbiota alterations are widely observed in schizophrenia patients and may account for various biological alterations involved in the cause of schizophrenia [45]. Recent study found that there was a drug-refractory form of schizophrenia for which the composition of gut microbiota was responsible [46].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…However, in a GM analysis of 90 medication-free patients with schizophrenia vs. 81 controls, it was observed that the first group presented differences in SCFAs, and neurotransmitters degradation or synthesis; therefore, at least some changes exist prior to the onset of the antipsychotic treatment in schizophrenia (70). GM in schizophrenia may be associated with neurostructural changes, psychopathology severity, subclinical inflammatory processes, and higher cardiovascular risk (71). Germ-free mice receiving fecal microbiome transplants (FMT) from patients with SSD had lower glutamate and higher glutamine/GABA concentrations in the hippocampus vs. healthy controls (72).…”
Section: Schizophrenia Spectrum Disordersmentioning
confidence: 99%